Burnout among nurses working in COVID-19 pandemic - Tri Ismu Pujiyanto; Fery Agusman Motuho Mendrofa; Umi Hani (Intelektual Pustaka Media Utama, 2022)
Nurses are at high risk of burnout because of the characteristic of their work that expends most of the time in delivering care to the patients. This study aimed to describe burnout among nurses working during corona virus disease 2019 (COVID-19) using nurses' demographic characteristics. This observational cross-sectional study involved 149 nurses from some hospitals and public health centers in Semarang using an online questionnaire from May 1 to June 15, 2020. Primary data were collected using Maslach Burnout Inventory including emotional exhaustion, depersonalization, and reduced personal accomplishment. Univariate and multivariate analyses were performed. The study showed that 63.6% of nurses in the COVID-19 unit were at high levels of emotional exhaustion, 56.3% of them were at high levels of depersonalization, and 46.7% of them are at high levels of reduced personal accomplishment. Education was the only demographic factor that was significantly related to emotional exhaustion and depersonalization (p<0.05) with a weak correlation. The work environment and the reduced anxiety-related factors were not significantly correlated with the reduced personal accomplishment with a very weak correlation, while the nurses’ unit was significantly correlated with depersonalization (p<0.05) with a very weak correlation. The results found that burnout develops among nurses due to the work environment-related factors such as the unit of work, corona-infected patients, personal protective equipment usage, and the specific characteristics of the workplace. Nurses’ characteristics affect their ability to manage the workload even in a pandemic. Nurses need optimal supports to build their self-efficacy. The organizational efforts play an important role in strengthening nurses to prevent burnout.